Systems approach to end-of-life management of residential photovoltaic panels and battery energy storage system in Australia. (December 2020) - Salim, H.K.; Stewart, R.A.; Sahin, O.; Dudley, M.
Abstract: Understanding the complexities around managing the end-of-life (EoL) residential solar photovoltaic (PV) and battery energy storage systems (BESS) is a precursor to a better decision-making process that mitigates unintended product life-cycle impacts. In this paper, a participatory Systems Thinking approach was utilised to build a causal loop diagram (CLD) for this system based on the collective knowledge of stakeholders. The developed CLD was categorised into three sub-systems: (1) waste flows; (2) regulatory aspects; and (3) industry strategies and government incentives. Two main system archetypes were identified in a reflection to the CLD, namely fixes that fail and drifting goals . The identified feedback loops indicate the need to introduce a comprehensive national product stewardship scheme, complimentary landfill restrictions, and provide sufficient incentives to industries for promoting recovery activities within residential PV panels and BESS sectors. An effective waste management system for these renewable energy technologies is most effective if industries are required to participate through regulation which also specifies certain targets, such as product and material recovery rates and establishes a sustainable funding model to meet operational requirements and future needs. The increasingly prohibitive overseas waste export market will require local industries and governments to collaboratively improve domestic recycling capability and capacity. In this light, the failure to build an effective EoL management system for residential PV and BESS will result in valuable and hazardous materials in both technologies to be disposed of in the landfill, stockpiled or illegally dumped; consequently, reinforcing unintended and adverse environmental impacts. Highlights: Causal loop diagram mapped the complexity of EoL management system of PV and BESS. Stakeholders were consulted to develop and validate the conceptual model. Conceptual model is governed by three subsystems and 13 feedback loops. Two system archetypes were identified, namely fixes that fail and drifting goals.